Il paradosso del gusto. Forme visibili dell’apprezzamento estetico - Fele, Giolo (SocietàMutamentoPolitica, 2016)
The subject of the article concerns the use of video to document the constitution and the production of a judgment of taste. Far from neurological or psycho-physiological concerns, the article is based on ethnomethodological premises to empirically study some basic philosophical themes: how a judgment of taste based on subjective and personal experience can aspire to a level of objectivity? In what way a judgment based on subjective and personal experience can aspire to a level of generality, that is, how are categories and formulations shared and acknowledged in a circle of mutual recognition? In what way can a judgment based on subjective and personal experience aspire to a level of commonality? The case empirically analyzed concerns the recognition of an olfactory object in a group of untrained tasters. The objectivity of judgment, the object recognition and the inter-subjectivity of experience are the features of the tasting and the basis of the judgment of taste that a multimodal analysis allows to analyze and to disentangle as under a microscopic lens.